Patent iliolumbar artery increase no risk of type II endoleaks after endovascular abdominal aortic aneurysm: a case-control study - Chen, Guo Xin; Liu, Dan; Weng, Chengxin; Chen, Chuwen; Wan, Jianghong; Zhao, Jichun; Yuan, Ding; Huang, Bin; Wang, Tiehao (Frontiers in Cardiovascular Medicine, 2023)
Objective The aims of the present study were to explore the risk factors for type 2 endoleaks (T2ELs) after endovascular aneurysm repair (EVAR) and the association between T2ELs and the iliolumbar artery. Materials and methods A single-center, retrospective case–control study in West China Hospital was conducted among patients with infrarenal abdominal aortic aneurysm (AAA) who underwent EVAR between June 2010 and June 2019. The associations of patient characteristics, anatomical factors, internal iliac artery embolization, and ILA with the primary outcome were analyzed. The secondary objective was to analyze survival and reintervention between the T2EL group and the non-T2EL group. Kaplan–Meier survival, propensity matching analysis and multivariate logistic regression analysis were used. Results A total of 603 patients were included. The median follow-up was 51 months (range 5.0–106.0). There was a significant difference in the diameter of the lumbar artery (LA), middle sacral artery (MSA) and inferior mesentery artery (IMA), proportion of thrombus and LA numbers. The univariate analysis showed that T2ELs were more likely to develop more thrombus in aneurysm cavity (OR = 0.294, p = 0.012), larger MSA (OR = 1.284, p = 0.04), LA (OR = 1.520, p = 0.015), IMA (OR = 1.056, p < 0.001) and more LAs (OR = 1.390, p = 0.019). The multivariate analysis showed that the number of LAs (HR: 1.349, 95% CI: 1.140–1.595, p < .001) and the diameter of the IMA (HR: 1.328, 95% CI: 1.078–1.636, p = 0.008) were significantly associated with T2ELs. There were no new findings from the propensity score matching. The reintervention-free survival rates were significantly different between the two groups (p = 0.048). Overall survival and AAA-related death rates were not different between the two group. This was consistent with the PSM analysis. Conclusion The iliolumbar artery and the different internal iliac artery interventions may not increase the incidence of T2ELs. But the numbers of LAs and IMA diameter were independent risk factors for T2Els. T2ELs was associated with the reintervention but did not affect long-term survival or increase aneurysm-related mortality after EVAR.